PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN KOMITE FARMASI NASIONAL - Siagian, Ade Onny; Suhendri; Haudi; Wijoyo, Hadion (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine: (1) The effect of work motivation on the performance of the Secretariat Of The National Pharmaceutical Committee Of The Republic Of Indonesia, (2) The effect of work discipline on employee performance.. National Pharmaceutical Committee Of The Republic Of Indonesia. This research is a survey research with a quantitative approach. The sample of this research is the employees of the Secretariat of the National Pharmacy Committee of the Ministry of Health, totaling 60 employees with a proportional random sampling technique. Data collection used a questionnaire while data analysis was performed using multiple regression analysis.The results of the study found that: (1) Work motivation has a t value of 2.551 with a significance level of 0.015 so that it is known that tcount> ttable (2.551> 2000), and a significance level of 0.015 <0.05. Which means that work motivation (X1) has a significant effect in a positive direction on employee performance at the National Pharmacy Committee of the Ministry of Health of the Republic of Indonesia (Y). (2) Work Discipline has a t value of 2.119 with a significance probability level of 0.039 So that it is known that tcount> ttable (2119> 2000), and a significance level of 0.039 <0.05, which means that Work Discipline (X2) has a significant effect in a positive direction on performance. Employees at the National Pharmacy Committee of the Indonesian Ministry of Health. (3) The work environment has a value of t count 13,000 with a probability level of significance of 0.000 So that it is known that tcount> ttable (13,000> 2000), and a significance level of 0,000 <0.05, which means that the Work Environment (X3) has a significant effect in a positive direction on performance. Employees at the National Pharmacy Committee of the Indonesian Ministry of Health.